2016
DOI: 10.1016/j.jsbmb.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of 25(OH) Vitamin D concentrations in Punjabi Sikhs: Results of the Asian Indian diabetic heart study

Abstract: Vitamin D deficiency is implicated in multiple disease conditions and accumulating evidence supports that the variation in serum vitamin D (25(OH)D) levels, including deficiency, is under strong genetic control. However, the underlying genetic mechanism associated with vitamin 25(OH)D concentrations is poorly understood. We earlier reported a very high prevalence of vitamin D deficiency associated with an increased risk for type 2 diabetes and obesity in a Punjabi Sikh diabetic cohort as part of the Asian Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 44 publications
(63 reference statements)
2
41
1
Order By: Relevance
“…Another association with a locus was suggested at rs11586313 in the regulatory region of the IVL gene located on chromosome 1q21.3. In addition, this study replicated known genes related with serum 25(OH)D concentrations adjusted for age, gender, body mass index, and type 1 diabetes status including GC (rs2282679) and CYP2R1 (rs12794714) reported in Europeans and the DAB1 (rs6680429), reported in Hispanics (Sapkota et al, ).…”
Section: Genetic Studies Of Vitamin Dsupporting
confidence: 73%
“…Another association with a locus was suggested at rs11586313 in the regulatory region of the IVL gene located on chromosome 1q21.3. In addition, this study replicated known genes related with serum 25(OH)D concentrations adjusted for age, gender, body mass index, and type 1 diabetes status including GC (rs2282679) and CYP2R1 (rs12794714) reported in Europeans and the DAB1 (rs6680429), reported in Hispanics (Sapkota et al, ).…”
Section: Genetic Studies Of Vitamin Dsupporting
confidence: 73%
“…In Table 5, we showed that DL-GAP2 and DAB1 were involved with diabetes mellitus [25, 26]; HOXC4, HOXC5, and HOXC6 were related to obesity and fat accumulation in differentiated brown adipocytes [27-30]; MECOM was associated with hypertension [31]. It is interesting to note that, of these 288 DMPs, two probes (cg22151644 and cg18473521) were both annotated to gene HOXC4.…”
Section: Resultsmentioning
confidence: 99%
“…According to the latest conducted genome-wide association studies and candidate gene studies [19][20][21][22], some of the most remarkable associations include genes such as Hydroxyvitamin D-1-α hydroxylase (CYP27B1), vitD 25-hydroxylase (CYP2R1), vitD binding protein (DBP/GC), vitD receptor (VDR), vitD 24-hydroxylase (CYP24A1), 7-dehydrocholesterol reductase (DHCR7), retinoid X receptors (RXR), calcium-sensing receptor (CASR), NPY, FOXA2, SSTR4, and IVL. Several review articles illustrating and detailing all these findings have been published by Jolliffe et al [18] and by Bahrami et al [17].…”
Section: Genetic Mechanisms Influencing Vitd Statusmentioning
confidence: 99%